Distributor, Sales Agent Or Own Subsidiary In The Export Choice? - YAP, ENG SENG (2010)
Company X is a US multinational pharmaceutical excipient company. It currently exports its product in Southeast Asia through various channels, by either distributor, sales agent or its own subsidiary. The choice of international distribution channels is of paramount importance to any industrial firm and a mistake in choice can be extremely costly to overcome in terms of time, resources and market opportunities. Not contented with the recent sales performance, the management team of Company X is tasked to analyse the best export mode for each of these countries given their apparent differences in business environment, political structure and financial risk. The aim of this study is to identify the right export mode, using the strategic rule. A number of hypothesis have been discussed in the past research to address this issue, with the notable ones being transaction cost economics, internationalization, resource-based, strategic and other propositions. However, transaction cost economic is the only theory that has been tested extensively and supported with relatively more positive empirical results. To achieve the study objective, an eclectic model combining transaction economic, resourced-base and strategic theories is used by the author for the case study. Model from Aulakh and Kotabe (1997) has been adopted and extended in order to apply a comprehensive and systematic approach that guides a rationale analysis of the external forces and internal influences, which provides a useful tool to decide the degree of integration in the export channel that can best fit the company and its offering. The results pointed to the fact that, in the medium to long term, Indonesia, Singapore and Vietnam markets appear to be attractive. For Singapore, the market stability and low external uncertainties has made it suitable to establish own subsidiary. As for Indonesia and Vietnam, it is more appropriate to distribute through the sales agents at this point in time, due largely to the country risks, volatility and diversities in those market. For the rest of the countries that are in the low market growth position, channel design in the form of sales agent or distributor is preferred. Export channel structure is not only critical at the establishment of marketing abroad, periodic review and evaluation of the structure is just as important as the business environment is changing faster than ever. Having the framework as the core, using multidimensional approach for decision making in a systematic and procedural way is confirmed to be useful to managers in practice.